JFGI: FROM DISTRIBUTED COGNITION TO DISTRIBUTED RELIABILISM - Michaelian, Kourken (Philosophical issues, 2014)
While, prima facie, virtue/credit approaches in epistemology would appear to be in tension with distributed/extended approaches in cognitive science, Pritchard (2010) has recently argued that the tension here is only apparent, at least given a weak version of distributed cognition, which claims merely that external resources often make critical contributions to the formation of true belief, and a weak virtue theory, which claims merely that, whenever a subject achieves knowledge, his cognitive agency makes a significant contribution to the formation of a true belief. But the significance of the role played by the subject’s cognitive agency in distributed cognitive systems is in fact highly variable: at one extreme, formation of a true belief seems clearly to be significantly creditable to the subject’s agency; at the other extreme, however, the subject’s agency plays such a peripheral role that it is at best unclear whether it should receive significant credit for formation of a true belief. The compatibility of distributed cognition and virtue epistemology thus turns on what it takes for a contribution to the formation of true belief to count as significant. This article argues that the inevitable vagueness of this notion suggests retreating from virtue epistemology to a form of process reliabilism and explores the prospects for a distributed reliabilist epistemology designed to fit smoothly with distributed cognition. In effect, distributed reliabilism radicalizes Goldberg’s recent extended reliabilist view (Goldberg 2010) by allowing the process the reliability of which determines the epistemic status of a subject’s belief to extend to include not only processing performed by other subjects but also processing performed by non-human technological resources.